Proteomic and Metabolomic Profiling of Deinococcus radiodurans Recovering After Exposure to Simulated Low Earth Orbit Vacuum Conditions - Ott, Emanuel; Kawaguchi, Yuko; Özgen, Natalie; Yamagishi, Akihiko; Rabbow, Elke; Rettberg, Petra; Weckwerth, Wolfram; Milojevic, Tetyana (Frontiers in Microbiology, 2019)
The polyextremophile, gram-positive bacterium Deinococcus radiodurans can withstand harsh conditions of real and simulated outer space environment, e.g., UV and ionizing radiation. A long-term space exposure of D. radiodurans has been performed in Low Earth Orbit (LEO) in frames of the Tanpopo orbital mission aiming to investigate the possibility of interplanetary life transfer. Space vacuum (10−4–10−7 Pa) is a harmful factor, which induces dehydration and affects microbial integrity, severely damaging cellular components: lipids, carbohydrates, proteins, and nucleic acids. However, the molecular strategies by which microorganisms protect their integrity on molecular and cellular levels against vacuum damage are not yet understood. In a simulation experiment, we exposed dried D. radiodurans cells to vacuum (10−4–10−7 Pa), which resembles vacuum pressure present outside the International Space Station in LEO. After 90 days of high vacuum exposure, survival of D. radiodurans cells was 2.5-fold lower compared to control cells. To trigger molecular repair mechanisms, vacuum exposed cells of D. radiodurans were recovered in complex medium for 3 h and 6 h. The combined approach of analyzing primary metabolites and proteins revealed important molecular activities during early recovery after vacuum exposure. In total, 1939 proteins covering 63 % of D. radiodurans annotated protein sequences were detected. Proteases, tRNA ligases, reactive oxygen species (ROS) scavenging proteins, nucleic acid repair proteins, TCA cycle proteins, and S-layer proteins are highly abundant after vacuum exposure. The overall abundance of amino acids and TCA cycle intermediates is reduced during the recovery phase of D. radiodurans as they are needed as carbon source. Furthermore, vacuum exposure induces an upregulation of Type III histidine kinases, which trigger the expression of S-layer related proteins. Along with the highly abundant transcriptional regulator of FNR/CRP family, specific histidine kinases might be involved in the regulation of vacuum stress response. After repair processes are finished, D. radiodurans switches off the connected repair machinery and focuses on proliferation. Combined comparative analysis of alterations in the proteome and metabolome helps to identify molecular key players in stress response of D. radiodurans, thus elucidating the mechanisms behind its extraordinary regenerative abilities and enabling this microorganism to withstand vacuum stress.